Physico-chemical characteristics of carrageenan/polyethylene oxide (PEO) hydrogel as an intelligent polymer - Mateo, Rosa Angelica M.; Mateo, Sonia Y. (2003)
ABSTRACT This thesis evaluates the physico-chemical characteristics of hydrogels subjected to four different treatments. When varying blends of carrageenan and polyethylene oxide (PEO) (w/w) were combined in a mixture, hydrogels were formed. These hydrogels were irradiated at varying doses to induce radiation cross-linking to make tougher gels. The irradiated hydrogels were then dried to constant weight and allowed to swell at three different ionic strength (0.01 M NaCl,0.1 M NaCl, 1 M NaCl) with constant 0.2 M NaCl at 37°; five different pH (pH 2, pH 4, pH 6, pH 8, pH 10) with constant 0.2 M NaCl at 37°C, and four different temperatures (5°C, 37°C, 50°C, 70°C) with constant pH 7 and no ionic strength. To analyze the variation on its swelling properties, the swelling ratio (change in weight after the equilibrium swelling divided by the initial weight) was calculated and graphed as dependent on the said treatments. Statistical analysis assessed the intelligence of the polymers. The SPSS 10.0 Program for Windows^TM was used to analyze the results of the equilibrium swelling ratio (%) of the hydrogel as a function of different treatments at varying doses. The Multiplier Linear Regression and One-Way Model of ANOVA (Analysis of Variance) was used to test the relationship between the dependent variables and the various treatments. There were 420 factors considered in this study. Based on the results of experiments, under the conditions of this study, the coefficients of the independent variables as opposed to the swelling ratio (dependent variable is represented by the mathematical model: Swelling ratio (%) = 296.821 (dose of treatment) - 1112.17 (M NaCl) - 44.194 (pH) - 3.84 (temperature) - 14.28 (PEO) + 142.717 (Kappa_Iota). Two major findings were thus, obtained. (1) The dose of radiation treatment and the type and concentration of carrageenan have significant effects on the swelling behavior of hydrogels. (2) Kappa carrageenan have better swelling capacity than iota carrageenan. In food systems, hdrogels may be applied as edible food films such as: gelatin, capsules, sausage casings, chocolate/sugar coatings, and wax coatings. If the hydrogel swells at different pH, ionic strength, temperature, dose of radiation, different concentrations of polyethylene oxide, type and different concentrations of carrageenan, it may be used to control the textural properties of food like fruits and vegeta
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Colloids; Carrageenan